Facile Synthesis of Cobalt Oxide as an Efficient Electrocatalyst for Hydrogen Evolution Reaction - Wu, Yinbo; Sun, Ruirui; Cen, Jian (Frontiers in Chemistry, 2020)
Hydrogen evolution reaction (HER) is receiving a lot of attention because it produces clean energy hydrogen. Catalyst is the key to the promotion and application of HER. However, the precious metal catalysts with good catalytic performance are expensive, and the preparation process of non-precious metal catalysts is extremely complicated. The simple preparation process is the most important problem to be solved in HER catalyst development. We synthetized cobalt oxide (CoOx) catalyst for HER through a simple hydrothermal process. The CoOx catalyst shows excellent HER catalytic activity. Characterization results reveal that there are a great deal of surface hydroxyl groups or oxygen vacancy on the surface of CoOx catalyst. In alkaline media the CoOx catalyst shows an over-potential of 112 mV at 20 mA cm-2 and a small Tafel slope of 94 mV dec-1. This paper provides a simple and easy method for HER catalyst preparation.